The effect of corporate social responsibility disclosure on stock prices through financial performance - Rizqy Aiddha Yuniawati (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of the relationship between Corporate Social Responsibility Disclosure on stock prices through the financial performance of go public companies listed in LQ 45 on the Indonesia Stock Exchange in 2019-2021. Focus on publicly traded companies that are listed in BEI under index LQ 45 enables specialised analyses relevant to Indonesian context. Indeks LQ 45 comprises 45 stocks with the highest liquidity in Indonesian stock markets and is widely regarded as a benchmark. In a specific subset of businesses, research on the relationship between CSR practise, financial performance, and stock price can provide valuable insights on local dynamics and investor sentiment related to CSR practises. Path analysis has been used as the analytical technique in this study. The study's variables include stock prices as the dependent variable, the profitability ratios ROE, ROA, and EPS as an intermediary variable, and Corporate Social Responsibility Disclosure as an independent variable. Using a sample of 23 businesses, it was discovered that: (1) Corporate Social Responsibility Disclosure has a significant impact on stock prices; (2) Corporate Social Responsibility Disclosure has a significant impact on ROE and ROA but not EPS; and (3) Corporate Social Responsibility Disclosure does not have a significant impact on stock prices when financial performance is used as an intermediary variable, represented by the ratio of ROE, ROA, and EPS.